APPLICATION OF EDIBLE COATING BREADFRUIT STARCH AGAINST CAYENNE PEPPER - Inawaty Sidabalok; Eddwina Aidila Fitria; Andal Susanto; Indira Karina (Department of Agroindustrial Technology, Bogor Agricultural University, 2023)
This study aimed to determine the effect of edible coating of breadfruit starch on the quality of cayenne pepper and to find out how long the optimal storage of cayenne pepper coated with an edible coating breadfruit starch and stored at room temperature. This study used a complete randomized design with 5 treatments and 3 data tests. The observation results were analyzed using ANOVA and the continued test DNMRT at the rate of 1%. The treatment in this study was the duration of storage of cayenne pepper coated with edible coating for 3, 6, 9, 12, and 15 days. The results showed that the length of storage of cayenne pepper coated with edible coating had a significant effect on water content, vitamin C, pH, and weight loss. Based on the color and texture test results of cayenne pepper coated with edible coating, it was shown that storage up to day 3 was most preferred by the panelists, with a moisture content of 85.32%, vitamin C content of 268.36 mg/100 g, pH of 3.35, and weight loss of 22.44%. Keywords: edible coating, breadfruit starch, cayenne pepper